THE SUBJECT OF THE INVENTION IS AN AERO POWER UNIT WITH (JET, ENGINE OR ELECTRIC) POWER DRIVE AND EQUIPMENT FOR PARACHUTES AND PARAGLIDERS - Mazurkiewicz, Zbigniew, Wladyslaw (2022)
Aero power unit with drive and equipment. Construction and method of folding and unfolding/opening of the unit for a parachute jump and for a gliding flight consisting in the use of draw-out arms (2) of engine fixing booms (1) or hinge fixed arms maintaining the drives/engines (1) in a respectively arranged position in relation to the jumper's body to ensure the dimensions and balancing the system weight in a way which enables a parachute jump. Vertically and horizontally tilting (x, y) fixing of the power unit to achieve the dimensions in the folded position allowing for a parachute jump and, during flight in an open main or spare canopy, better manoeuvring/agility possibilities for the parachutist and to obtain the possibility to compensate negative outside aspects, such as for example wind, by fixing the thrust corresponding to the situation/power unit angle. The use of the chest module (4) as a container for a battery or a fuel tank depending on the type of used engines.